MENGUNYAH SENSUALITAS: Resepsi Khalayak Terkait Konten Pornomedia Bigo Live - Yulianti, Athaya Hasna (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
Nowadays, many social media compete to present the features to fulfill the wishes and entertainment for the audience. One of them, the presence of video live streaming features that can be found in some applications. Bigo Live is one of the applications with live streaming video feature whose presence controversy. This is because many sexually explicit and pornographic content on Bigo Live application, which is done by the host or the broadcaster. The videos were aired live, show the sensuality aspects that can be sexually provoke the audiences. It also can not be separated from the role of the audience, by providing negative comments referring to the direction of pornography. This research is based from the use and acceptance by the audience as viewers, which aims to find out how the viewers reception to the content of porno-action and pornography on Bigo Live application. This research using qualitative approach, with Stuart Hall’s reception analysis to find out the decoding position of four informants. The result of the research found out that there’s one informant with dominant-hegemonic position, it means the informant receive and interpret messages of porno-action and pornography on Bigo Live fully with no rejection. Then, there are two informants, those who are in negotiated position, which means they understand the message of porno-action and pornography but not fully accepted because they have their own beliefs. The last one, is one informant in the oppositional position that receive and understand the code of the message, but rejected the whole idea of porno-action and pornography on Bigo Live. The three decoding position on the informants, was influenced by three factors, there are framework of knowledge, relations of production and technical infrastructure.